2007
DOI: 10.1111/j.1365-2745.2006.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rooting volume and nutrient availability as an alternative explanation for root self/non‐self discrimination

Abstract: 1 An increasing number of studies have shown that plants produce more root mass when sharing rooting space with an intraspecific neighbour as compared with plants growing alone. This so-called self/non-self discrimination has been suggested as a mechanism by which plants may prevent wasteful competition with their own roots and enhance their competitive ability for nutrients with roots of neighbouring plants. The overproduction of root biomass is said to result in a 'tragedy of the commons', because it appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
210
6
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(232 citation statements)
references
References 32 publications
12
210
6
4
Order By: Relevance
“…Despite its putative ecological and evolutionary relevance, the significance of root recognition is largely unknown and has been examined in a limited number of studies (Hess & de Kroon 2007). Dudley and File's experiment found signs of kin recognition through root interactions, but did not detect any effect on individual or group fitness (Dudley & File 2007) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its putative ecological and evolutionary relevance, the significance of root recognition is largely unknown and has been examined in a limited number of studies (Hess & de Kroon 2007). Dudley and File's experiment found signs of kin recognition through root interactions, but did not detect any effect on individual or group fitness (Dudley & File 2007) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Trees either invest more carbon underground to increase fine root biomass and production, or improve their nutrient and water uptake efficiency from the soil by changing root morphology. A number of studies have demonstrated that fine root biomass and morphology are closely related to tree species and stand ages [14,35]. Thus, estimating changes in underground biomass, production, and morphology is crucial to understand the fine root dynamics and processes in the development of forest ecosystems.…”
Section: Fine Root Morphologymentioning
confidence: 99%
“…This is in agreement with the result of Fu et al [34] that C. lanceolata seedlings in different stand types, that were studied together for 2-year-old, were dominant in Huitong. It is likely that the root grew first in the resource hotspot in the young stands, and the plant could maximize the nutrient return to supply the plant growth; when experiencing stress in space, nutrients and moisture, the plants were forced to invest more carbon to roots for nutrient and water absorption in 17-year-old and 25-year-old plantations [35].…”
Section: Fine Root Biomass and Necromassmentioning
confidence: 99%
“…Occasionally, the issue of pot size has received attention in other fields of plant biology. Arp (1991), for example, emphasised that pot size might be an important issue in experiments that considered the effect of elevated CO 2 on plants; and recently, a discussion in the field of ecophysiology has emerged, where studies on the recognition of roots of neighbours are thought to be confounded by pot size (Hess and De Kroon 2007).…”
Section: Introductionmentioning
confidence: 99%